(untitled) (Journal of Medicine, 2016)
Background: The immune status is usually hampered in patients of diabetes mellitus. The global pandemic of diabetes principally involves type 2 diabetes. In diabetic patients higher prevalence of hepatitis B virus infection is also noted that leads to more severe complications. This study was conducted to determine the immune responses to hepatitis B vaccine in type 2 diabetic patients. Methods: In this study 33 diabetic patients were included as experimental group and 34 non diabetic healthy persons were included as control group. All the participants were vaccinated with hepatitis B vaccine following 0, 1, 6 months schedule. The vaccine responses in diabetic and non diabetic group were compared depending on seromarkers (anti-HBs titer, IL-2 and IFN-?) following vaccination. Results: The mean value of anti-HBs titer was lower in diabetic group (357.81 mIU/ml) than non diabetic group (621.24 mIU/ml) but the difference was not significant (p>0.05), the mean value of IFN-? was lower in diabetic group (0.1480 IU/ml) than non diabetic group (0.2788 IU/ml) and here the difference was significant (p<0.05), the mean value of serum IL-2 level was also lower in diabetic group (0.2611IU/ml) than non diabetic group (0.3691 IU/ml) but the difference was not significant (p>0.05). Conclusion: The study revealed no statistically significant variation in anti-HBs and IL-2 but a diminished IFN-? level as the immune response in diabetic patients after HBV infection. J MEDICINE January 2016; 17 (1) : 8-11